C‐reactive protein inhibits C3a/C3aR‐dependent podocyte autophagy in favor of diabetic kidney disease. Issue 6 (3rd May 2022) - Zhang, Lin; Li, Wei; Gong, Minjie; Zhang, Zeyu; Xue, Xiaodong; Mao, Jiarong; Zhang, Haibao; Li, Siqi; Liu, Xiawan; Wu, Feng; Shi, Jingming; Fu, Guorong
Abstract: Numerous studies have reported the pathogenic roles of C‐reactive protein (CRP) and complement activation in diabetic kidney disease (DKD) individually. However, considering the potent regulatory effect of CRP on complement activation, it remains unclear whether CRP participates in DKD pathogenesis by regulating complement activation. Moreover, this work focuses on complement activation in rats, which aims at settling the dispute that whether rat CRP can activate the complement system. To address this question, the complement effectors C3a, C5a, and C5b‐9 were examined in human patients with diabetic nephropathy (DN) and wt, Crp −/−, and huCRP tg rats with STZ‐diabetic DKD. The Crp −/− rats showed more C3a accumulation in blood and glomeruli than wt and huCRP tg rats. The balance between autophagy and apoptosis was evaluated in DKD rats, and Crp −/− rats showed increased podocyte autophagy compared with wt and huCRP tg rats. Meanwhile, stable CRP‐overexpression and CRP‐knockout cell lines were established and used to demonstrate that CRP suppresses C3a‐induced podocyte autophagy under high‐glucose conditions. We further verified that the inhibition of C3a‐induced podocyte autophagy by CRP was dependent on C3aR expression and that this effect could be reversed with a C3aR antagonist and agonist. Therefore, our findings provide evidence that CRP suppresses podocyte autophagy to accelerate the development of DKD by inhibiting C3a/C3aR axis signaling, which may help in the development of a new therapeutic strategy for the management of podocyte autophagy and DKD. In addition, rat CRP has been shown to be identical to human CRP in the activation of autologous complement and interspecific complement.